Estudio definitivo de la carretera Sangamayoc – Nueva Libertad - Yrigoin Bustamante, Jose Edilberto (2000)
The present work of thesis to obtain the professional title of Civil Engineer, has been developed in order to make a scientific contribution to help solve a problem of local roads, that will provide a road section which contributes to the socioeconomic development of the beneficiaries to be executed. The research is applied and it has been conducted at the Faculty of Civil Engineering, Universidad Nacional de San Martín, developing the project in the province of Lamas, area of the Huallaga Central special project and under may. This work has been developed by applying the field theories and existing standards of topography, soils, hydrology, environmental impact, drainage mechanics road, concrete and other similar ones, and that have allowed to have the definitive study of the road section already named. The results obtained demonstrate clearly that it is possible to achieve, through the correct application of the te...